Accuracy of automated urine dipstick test as a screening tool for proteinuria in hypertensive disorders of pregnancy - Sundaram, Sankar; Kuriakose, Ann Mili; P., Vijayan C. (International Journal of Research in Medical Sciences, 2020)
Background: Progressive proteinuria implies worsening of the condition in hypertensive disorders of pregnancy and hence its quantification guides clinician in making decision and planning treatment. The gold standard is 24 hour urine protein estimation. Urine sediment cytology, also known as ‘liquid renal biopsy’ identifies and analyses the extent of renal damage. Methods: Objectives of the study were to compare the efficacy of urine dipstick test to 24 hour urine protein estimation in detecting proteinuria in pre-eclampsic patients and to describe the findings in urine sediment examination in assessing proteinuria in above patients. Urine dipstick test and sediment cytology were performed on the urinary samples of 242 pregnant women with high BP recordings (BP>140/90 mm Hg) which were collected and tested in Department of Pathology, Government Medical College, Kottayam during the study period of 18 months. This was compared with 24 hour urine protein values (gold standard). Results: About 154 patients (63.63%) had significant proteinuria of more than 300mg/24hr. Dipstick method showed 78.57% sensitivity and 81.82% specificity for prediction of significant proteinuria. Positive predictive value and negative predictive value of urine dipstick test were 88.32% and 68.57% respectively. Urine sediment examination revealed the presence of casts only in 11.98% of study population. Conclusions: Diagnostic accuracy of automated urine dipstick test in assessing proteinuria was 79.75%. For grade 1 proteinuria, diagnostic accuracy was 79.81%, for Grade 2 it increased to 93.14% and for grade 3 & 4, accuracy was 98.68%. Urine sediment examination didn’t correlate with proteinuria and hence the extent of renal damage in pre-eclampsia.